Sociological inquiry results of internal consumers of PAS services on the prospects of regional pathology centers project - L. G. Rosha (Kazimierz Wielki University, 2018)
The aim is to research the value of the PAS's survey of domestic consumer services (DCS) regarding the promisingness of the project within the framework of PAS decentralization - the creation of a regional pathoanatomical center (RPC). Materials and methods. According to a specially worked out questionnaire, 205 DCS PAS were interviewed - doctors (oncologists, surgeons, chemotherapists). Statistical processing of the obtained results is carried out using generally accepted statistical methods. Results. The estimation of the project implementation perspective of the RPC is given, taking into account the current PAS state. Conclusions. The results of the study showed that the modern PAS system needs to be reformed.